IMPLEMENTASI KEBIJAKAN ANTI-BULLYING DALAM MENCIPTAKAN IKLIM AMAN DI MADRASAH TSANAWIYAH NEGERI 7 BUNGO - Amelia, Delvina; Hindun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The phenomenon of bullying in educational environments remains a serious problem because it negatively impacts the psychological, social, and academic conditions of students. Madrasahs, as religious-based educational institutions, have a strategic responsibility to create a safe and character-based learning environment. This study aims to analyze the implementation of the Anti-Bullying policy at Madrasah Tsanawiyah Negeri 7 Bungo, identify factors that influence its effectiveness, and examine its impact on creating a safe madrasa climate. This study uses a qualitative approach with a descriptive type. Data were collected through observation, in-depth interviews, and documentation with the madrasah principal, vice principal for student affairs, Guidance and Counseling teachers, homeroom teachers, and students. Data analysis was carried out through data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results of the study indicate that the Anti-Bullying policy at MTs Negeri 7 Bungo has been implemented through routine socialization, enforcement of discipline, teacher supervision, use of CCTV, implementation of a violation point system, and the habituation of religious character. Despite persistent barriers such as the perception of bullying as a joke, the influence of social circles, and limited supervision in some areas, this policy has been shown to reduce the intensity of bullying and increase students' sense of security. This research contributes to strengthening the practice of character-building-based anti-bullying policies in madrasah environments and collaboration between madrasahs and parents.